2016
DOI: 10.1177/1753495x15626623
|View full text |Cite
|
Sign up to set email alerts
|

Two case reports of generalized pustular psoriasis of pregnancy: Different outcomes

Abstract: Generalized pustular psoriasis of pregnancy is a rare dermatosis with potential serious consequences for both the mother and fetus. Treatment is difficult and historically steroids were the mainstay of treatment. Cyclosporin has been used for a few cases resistant to steroids. We report our own experience of two cases of generalized pustular psoriasis of pregnancy. Cases of generalized pustular psoriasis of pregnancy need review by a dermatologist with experience of skin disorders in pregnancy. Both the fetus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
0
24
0
2
Order By: Relevance
“…Although our patient was treated successfully with prednisone, some unresponsive cases to prednisone have been reported [ 13 - 15 ]. Successful treatment with cyclosporine has been reported and this regime can be used as second line treatment [ 6 , 16 , 17 ]. Antibiotics may be used to prevent and treat infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although our patient was treated successfully with prednisone, some unresponsive cases to prednisone have been reported [ 13 - 15 ]. Successful treatment with cyclosporine has been reported and this regime can be used as second line treatment [ 6 , 16 , 17 ]. Antibiotics may be used to prevent and treat infections.…”
Section: Discussionmentioning
confidence: 99%
“…10 Differing opinions exist as to whether personal or family history of psoriasis confers increased risk of GPPP. 7,10,11,12 Our patient had no personal or family history and reported complete resolution eight weeks postpartum with only faint post-inflammatory erythema.…”
Section: Whenmentioning
confidence: 78%
“…Numerous publications note rapid resolution of disease following delivery, but some reports suggest GPPP may recur in subsequent pregnancies. 10,11,12 In some instances it has been reported that the pustular form evolved into classic psoriatic lesions. 10 Differing opinions exist as to whether personal or family history of psoriasis confers increased risk of GPPP.…”
Section: Whenmentioning
confidence: 99%
“…Unlike many other dermatoses of pregnancy, which are usually limited to the skin, PPP is frequently accompanied by systemic signs and symptoms of fatigue, fever, diarrhea, delirium, elevated markers of inflammation such as an increased erythrocyte sedimentation rate, and increased white blood cell counts. 5 , 17 In severe cases, the rash of PPP can progress to erythroderma with resulting dangerous fluid and electrolyte imbalances, loss of thermoregulation in the skin, and the risk of secondary infection and sepsis. 18 …”
Section: Clinical Presentation Of Diseasementioning
confidence: 99%
“…In a large number of women with PPP, there is a positive personal or family history of psoriasis; nevertheless, there are still many cases without a known family history of psoriasis. 17 Hypoparathyroidism, hypocalcemia, stress, and infections have been suggested as potential triggers of PPP, although causal associations have not been elucidated. 16 , 18 In addition, if a woman develops PPP during one pregnancy, there is an increased risk of more severe outbreaks in subsequent pregnancies that may present earlier.…”
Section: Natural History Of Disease and Fetal Outcomesmentioning
confidence: 99%